Season Changeability and Condition of Newborns - Litwiejko-Pietryńczak, Elżbieta (Anthropological Review, 1996)
A group of 1913 40-weeks old, first-born and from subsequent pregnancies newborns (920 female and 993 male) from Białystok were examined with respect to the following anthropometric features: body mass, crown-rump length (si), head and chest circumference and their relation to the month of the children’s birth.